Physical properties and transmission spectrum of the WASP-74 planetary system from multiband photometry. Issue 4 (14th March 2019) - Mancini, L; Southworth, J; Mollière, P; Tregloan-Reed, J; Juvan, I G; Chen, G; Sarkis, P; Bruni, I; Ciceri, S; Andersen, M I; Bozza, V; Bramich, D M; et al.
Abstract: We present broad-band photometry of 11 planetary transits of the hot Jupiter WASP-74 b, using three medium-class telescopes and employing the telescope-defocusing technique. Most of the transits were monitored through I filters and one was simultaneously observed in five optical ( U, g ′, r ′, i ′, z ′) and three near-infrared ( J, H, K ) passbands, for a total of 18 light curves. We also obtained new high-resolution spectra of the host star. We used these new data to review the orbital and physical properties of the WASP-74 planetary system. We were able to better constrain the main system characteristics, measuring smaller radius and mass for both the hot Jupiter and its host star than previously reported in the literature. Joining our optical data with those taken with the HST in the near infrared, we built up an observational transmission spectrum of the planet, which suggests the presence of strong optical absorbers, as TiO and VO gases, in its atmosphere.